Relaksasi Kredit terhadap Debitur dimasa Pandemi Covid-19 di Koperasi Hening Rahayu Kabupaten Tabanan - Gusti Putu Ngurah Gita Pradnyana Putra; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2022)
The credit relaxation process for the Hening Rahayu Cooperative is a breath of fresh air for debtors who are in default during the COVID-19 pandemic. This study aims to analyze and describe credit relaxation for debtors during the COVID-19 pandemic at the Hening Rahayu Cooperative, Tabanan Regency. This research was conducted at the Hening Rahayu Cooperative in Tabanan Regency. This type of research uses empirical legal research, namely a problem approach that is seen in terms of legal rules with the facts on the ground.â€ The results obtained: The criteria for non-performing loans can be seen from if the debtor is unable to carry out his obligations as stated in the loan agreement. Handling non-performing loans with a credit relaxation process, which can be done by rescheduling, re-requirements, and restructuring.